2022
DOI: 10.1039/d1en00905b
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating heterogeneous iron biomineralization patterns in a denitrifying As(iii)-oxidizing bacterium: implications for arsenic immobilization

Abstract: Anaerobic nitrate-dependent iron(ii) oxidation is a process common to many bacterial species, which promotes the formation of Fe(iii) minerals that can influence the fate of soil and groundwater pollutants, such as arsenic.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Also, a microbial scenario of its formation, including the so-called forced biomineralization [ 70 ], is well documented in the literature. Bacterial biomineralization of lepidocrocite has been reported for diverse nitrate-reducing Fe(II)-oxidizing bacteria [ 71 ], as well as in denitrifying As(III)-oxidizing bacterium [ 72 ] under anaerobic conditions. Also, it was observed that iron oxyhydroxide crystallization could be directed during the cultivation of Leptothrix sp.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a microbial scenario of its formation, including the so-called forced biomineralization [ 70 ], is well documented in the literature. Bacterial biomineralization of lepidocrocite has been reported for diverse nitrate-reducing Fe(II)-oxidizing bacteria [ 71 ], as well as in denitrifying As(III)-oxidizing bacterium [ 72 ] under anaerobic conditions. Also, it was observed that iron oxyhydroxide crystallization could be directed during the cultivation of Leptothrix sp.…”
Section: Discussionmentioning
confidence: 99%
“…strain 2002 and Pseudomonas stutzeri LS-2), where cells were encrusted by forming Fe(III) minerals, leading to an incomplete reduction of nitrate [ 54 , 55 , 56 ]. In addition, the observed decrease in As(V) reduction in the presence of Fe(II) was also caused by the adsorption or co-precipitation with the formed Fe oxides, supported by the decrease of dissolved total As concentrations during incubation ( Figure S8 ) [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic has a very low background in biological systems, which makes it possible to use NanoSIMS to map the distribution of arsenic-containing molecules in cells and tissues with high resolution. 21,22 Correlative imaging methods have become important in mapping the chemical information from Nano-SIMS to the ultrastructural information from electron microscopy [i.e., transmission electron microscopy images or backscattered electron (BSE) images from a scanning electron microscope]. 20 Recently, subcellular distributions of drugs that contain platinum, 23−25 gold, 26,27 ruthenium, 28 bromine, 29−31 and iodine 32 have been mapped by NanoSIMS analysis in a label-free fashion, which demonstrated the capabilities of NanoSIMS analysis for investigating therapeutic subcellular partitioning.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The NanoSIMS instrument bombards cells with a 50 nm 133 Cs + beam, releasing negatively charged secondary ions that are collected, quantified, and used to create high-resolution images based solely on the elemental content of cells. , NanoSIMS analysis makes it possible to visualize (and quantify) therapeutic agents in biological systems without fluorescent labeling or with a minimum of elemental and isotopic labeling. Arsenic has a very low background in biological systems, which makes it possible to use NanoSIMS to map the distribution of arsenic-containing molecules in cells and tissues with high resolution. , Correlative imaging methods have become important in mapping the chemical information from NanoSIMS to the ultrastructural information from electron microscopy [ i.e. , transmission electron microscopy images or backscattered electron (BSE) images from a scanning electron microscope] .…”
Section: Introductionmentioning
confidence: 99%